Religiosity in the Midst of the Wage System and the Fading of Ti'ayo in Gorontalo Tradition - Arfan Nusi; Fahimah M. Mooduto; Donald Q. Tungkagi (Jurnal Theologia, 2020)
People are very thick with the religious practices which combine religion and culture in Gorontalo. One of the religious spirits in the tradition is ti'ayo (community self-help). It is a farmer comes to everyone. It offers requests for helping others in the context of working together without wages in their garden. This cycle always occurs between one farmer and other farmers for decades. In addition, cultivating the values of togetherness among farmers. Economically, ti'ayo tradition also reduces the cost of cultivating gardens. The source of the research was obtained from qualitative anthropological research. The data were obtained using observation techniques and in-depth interviews. The aim is to see wage practices amid the fading ti'ayo tradition in the society of Gorontalo. The result is people's religiosity is slowly getting weaker. It is indicated since ti'ayo tradition replaced with a wage system. It also usually strengthens relationships and harmony among people and maintains brotherhood. However, this tradition has not survived until now; it seems that the community is living individually, between one farmer and others as if they have lost their sensitivity. The effect is the difficulty of the farmers in maintaining its life amid the onslaught of the wage system. The economic constraints of farmers are increasingly complex, including the borrowing capital from creditors with guarantees of garden or rice fields, instead of getting benefits from the harvest; precisely, they have to pay for the debts.